2020
DOI: 10.1017/psrm.2020.32
|View full text |Cite
|
Sign up to set email alerts
|

We need to go deeper: measuring electoral violence using convolutional neural networks and social media

Abstract: Electoral violence is conceived of as violence that occurs contemporaneously with elections, and as violence that would not have occurred in the absence of an election. While measuring the temporal aspect of this phenomenon is straightforward, measuring whether occurrences of violence are truly related to elections is more difficult. Using machine learning, we measure electoral violence across three elections using disaggregated reporting in social media. We demonstrate that our methodology is more than 30 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…However, we need to expand inquiry into other arenas of violence. For example, social media forms a space for threats and intimidation during election periods (Muchlinski et al, 2019). Additionally, studies on the gendered impacts of electoral violence show how female voters and candidates often face violence in the private space of their home, away from the public limelight (Bardall, 2011; Bjarnegård, 2018).…”
Section: Looking Forwardmentioning
confidence: 99%
“…However, we need to expand inquiry into other arenas of violence. For example, social media forms a space for threats and intimidation during election periods (Muchlinski et al, 2019). Additionally, studies on the gendered impacts of electoral violence show how female voters and candidates often face violence in the private space of their home, away from the public limelight (Bardall, 2011; Bjarnegård, 2018).…”
Section: Looking Forwardmentioning
confidence: 99%
“…Machine learning and natural language processing were employed to monitor Twitter, looking for the existence of violent incidents (e.g., physical attacks on opposition politicians, violence between opposition and incumbent parties, candidate assassination) during the 2015 parliamentary election in Venezuela (Yang et al 2016). Also, in the context of the Venezuelan parliamentary election of 2015, Muchlinski et al proposed a neural networks approach to estimate forms of political violence from tweets (Muchlinski et al 2021). But researchers did not only introduce approaches to monitor electoral incidents through social media but also proposed mechanisms to report them.…”
Section: Offline Events and Social Mediamentioning
confidence: 99%
“…The sample representativeness of the general population of Twitter data is still debated, but it appears to be highly contingent on the research question. For certain topics, research has shown that Twitter is a credible source to reproduce real-world outcomes such as protest and violence (Muchlinski et al, 2021; Sobolev et al, 2020; Steinert-Threlkeld, 2018; Zhang & Pan, 2019). However, for other research questions, such as studying public opinion across the United States, we align with other scholars who express caution about extrapolating Twitter users’ opinions to other Americans, such as about people’s happiness level (Jensen, 2017).…”
Section: Data Qualitymentioning
confidence: 99%